2016
DOI: 10.1007/s11115-015-0340-0
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Networking and Stakeholder Support in Public Service Organizations

Abstract: Resource dependence theory suggests that to function successfully, organizations must obtain certain resources controlled by actors in their environment. To do this effectively, managers often develop networking relationships with key stakeholder groups in order to make critical resources available. Managers in public service organizations, in particular, are frequently under great pressure to network with relevant actors from stakeholder groups in order to build support for service (co)production and legitima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…However, the interviews revealed that in spite of a lack of organizational support, many of the respondents were aware that cooperation is an important source of knowledge on competency management. In this respect our study underlines the value of professional networks, which facilitate the transfer of best management practices into public administration as well as development of employee competencies and organizational competences (Andrews and Beynon, 2017). In line with this, we expect:Proposition The level of knowledge about competency management will grow with the frequency of relations of public officers with employees of organizations where competency management is successfully practised.…”
Section: Discussionmentioning
confidence: 76%
“…However, the interviews revealed that in spite of a lack of organizational support, many of the respondents were aware that cooperation is an important source of knowledge on competency management. In this respect our study underlines the value of professional networks, which facilitate the transfer of best management practices into public administration as well as development of employee competencies and organizational competences (Andrews and Beynon, 2017). In line with this, we expect:Proposition The level of knowledge about competency management will grow with the frequency of relations of public officers with employees of organizations where competency management is successfully practised.…”
Section: Discussionmentioning
confidence: 76%
“…The analysis resulted in differentiation between the clusters based on employees’ perceptions of their managers’ performances of all eight roles, which we term ‘integrated leadership-in-government’. The box plot 1 elucidation of clusters presented in Figure 1 shows the mean scores, across the eight roles, for the perceived performance of integrated leadership-in-government for each cluster (for previous use of this form of visualisation, see Andrews and Beynon, 2016; McDermott et al., 2013). The individual cluster means were found by aggregating the respondents’ response values based on their majority association to a cluster (for a respondent, the cluster with the highest associated membership coefficient is chosen as its majority association cluster).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Hierarchical regression analyses of the relationship between the five clusters and job satisfaction and self-perceived performance, taking into consideration other variables, are shown in Table 2. To facilitate the regression analyses, the five clusters were transformed into dummy variables using the membership coefficient values for the positive cluster values generated from the fuzzy c-means clustering, rather than a single positive value as would be the case for crisp-set clustering techniques (as developed by Andrews and Beynon (2016), building on Janssens et al (2003)). Five separate regression equations were calculated, with a different integrated leadership-in-government cluster used as a reference category for each model.…”
Section: Job Satisfaction and Self-perceived Performancementioning
confidence: 99%
“…Companies are more likely to display varied combinations of resource levels, and therefore, the fuzzy cluster analysis is performed on the assumption that each SME will be associated, to varying degrees, with different resource-based clusters. In this regard, cluster solutions were provisionally investigated with three, up to six clusters, with theoretical defence arguments, as well as granularity of cluster case membership suggesting that the five-cluster solution was appropriate for the analysis here (Andrews and Beynon, 2010, 2017; McDermott et al , 2013).…”
Section: Discussionmentioning
confidence: 99%